Disability Insurance Beneficiaries with Visual Impairments in Vocational Rehabilitation: Socio-demographic Influences on Employment. (November 2013) - Giesen, J. Martin; Cavenaugh, Brenda S.
Introduction: Given mutual concerns of vocational rehabilitation and the Social Security Administration, our purpose was to evaluate the effect of current individual and economic factors on competitive employment for Social Security Disability Insurance (SSDI) beneficiaries with visual impairments in vocational rehabilitation. Methods: Using fiscal year 2010 RSA-911 data on 4, 478 SSDI beneficiaries whose vocational rehabilitation services had concluded, we conducted descriptive and multilevel analyses to determine which client and state or agency factors predicted competitive employment. Results: Unemployment rate, gender, age, race, disability, severity of visual impairment, education, prior earnings, SSDI amount, and interactive effects of agency structure were significantly related to competitive employment. Discussion: This research provided new knowledge of state or agency influences, risk factors, advantages, and compensatory effects of services in blind agencies, and underscored the importance of prior work experience in achieving competitive employment for SSDI-beneficiary consumers. Implications for practitioners: Recommendations related to vocational rehabilitation services to SSDI beneficiaries, policy regarding agency structure, and future research are made.